Neuromarketing algorithms' consumer privacy and ethical considerations: challenges and opportunities - Marcus Goncalves; Yiwei Hu; Irene Aliagas; Luis Manuel Cerdá (Cogent Business & Management, 2024)
This research investigates the ethical and privacy issues arising from using AI andML in neuromarketing, framed by rule utilitarianism. It assesses the impact of these technologies on consumerprivacy and human rights through a combination of literature review, bibliometric analysis, and empirical data fromsurveys and interviews with experts in the US and Spain. The study reveals the tensions between the efficacy ofneuromarketing techniques and the imperative to protect consumer privacy, particularly in light of the GDPR'sinfluence on global practices. It emphasizes the need for internationally consistent ethical standards and consumerdata regulations, drawing from the comparative analysis of policies in the US and EU. The outcomes include policyrecommendations to minimize ethical risks and promote the responsible progression of neuromarketing. Theserecommendations guide companies and managers toward ethical transparency and accountability. Additionally, theresearch offers a policy framework for crafting ethical neuromarketing practices that reconcile technological progresswith consumer well-being, thereby contributing to broader discussions on embedding ethics within technological innovation.Advances in neurotechnology are revolutionizing marketing strategies, allowing businesses to predict and influence consumer behavior with remarkable accuracy. This paper investigates the ethical challenges and privacy concerns associated with using artificial intelligence (AI) and machine learning (ML) in neuromarketing. Through a comprehensive literature review and expert interviews, it explores how these technologies intersect with consumer rights and offers policy recommendations to address ethical dilemmas. This research examines the balance between marketing innovation and the safeguarding of individual privacy, contributing to the ongoing debate on the ethical use of AI in understanding consumer preferences.
Keywords: 650; Neuromarketing; neuroethics; AI/ML algorithms; GDPR; CCPA